Neuropharmacological Interventions in Alzheimer’s Disease: Current and Emerging Approaches - Lalit Parihar; Ajay Pal Singh; Sanjar Alam (Current Pharmacogenomics and Personalized Medicine, 2026)
Introduction:: Alzheimer’s Disease (AD) is a neurodegenerative disorder with progressive cognitive decline, β-amyloid plaques, neurofibrillary tangles, oxidative stress, and neuroinflammatory responses. So far, the pathogenesis of AD has been explained by the cholinergic hypothesis, amyloid cascade hypothesis, and tau protein dysfunction. However, the current pharmacological treatment of AD with cholinesterase inhibitors and NMDA receptor antagonists provides only symptomatic relief and cannot prevent the progression of the disease. Methods:: This review article discusses the recent developments in neuropharmacology in the treatment of AD with a focus on the discovery of novel therapeutic targets and innovative therapeutic strategies with multi-target pharmacology involving protein–protein interaction inhibitors, allosteric modulators, selective enzyme inhibitors, and proteolysistargeting chimeras (PROTACs), and the discovery of novel drug delivery systems to overcome the blood–brain barrier. Results:: Current preclinical and emerging evidence indicate that the modulation of interconnected pathological pathways, including mitochondrial dysfunction, insulin resistance, and neuroinflammation, may lead to improved therapeutic outcomes. Dual inhibitors of tau hyperphosphorylation and Aβ aggregation have been shown to improve therapeutic efficacy, while modulation of neurotrophic signaling pathways, including BDNF, has been shown to possess neuroprotective effects. Moreover, improved drug delivery systems across the BBB will enhance drug bioavailability, thereby increasing therapeutic efficiency. Discussion:: Despite the promising preclinical data, there are several challenges in translating these therapeutic interventions into clinical success in AD treatment due to the complexity of the disease, delayed diagnosis, and lack of predictive markers. The incorporation of early diagnostic biomarkers in conjunction with the use of multi-target therapy will improve therapeutic efficacy in the treatment of AD. Conclusion:: Neuropharmacological approaches, where various mechanisms of pathology are targeted, hold promise for developing disease-modifying treatments for AD. Further research in this area, incorporating innovative drug development techniques, drug delivery systems, and early intervention techniques, is crucial for better patient outcomes and slower disease progression.